TEACHING SPEAKING TO ADULT INDONESIAN LEARNERS IN ENGLISH CLASSROOM - Devika Adelita; Nirmawan Nirmawan; Abdullah Hasibuan (Linguistik : Jurnal Bahasa dan Sastra, 2026)
Speaking skills are the capabilities that enable efficient communication. They enable us to communicate verbally and in a way that is understandable to the listener. The objectives of this research were to find out the adult learners challenges in speaking and to investigate the teacher’s strategies to help students in speaking. Six adult students (four women and two men), all between the ages of 27 and 35 took part in this study using a qualitative case study approach. A semi-structured interview were employed as the data collection tools to examine the perspectives of the participants on the challenges they faced. Besides that, the researcher also done an observation to observe the teacher strategies in improving and helping students to speak. The findings indicated that adult learners face two difficulties: linguistic issues (pronunciation, grammar, vocabulary), and psychological issues (anxiety, lack of confidence, and lack of motivation) which vocabulary and pronunciation pose the greatest challenges while speaking. The second insight relates to the teacher's methods for enhancing and assisting his students' English-speaking abilities. The teacher employs three techniques: providing motivation, role playing, and storytelling.